The Impact of Interest Rates and Liquidity on Financial Stock Returns: Market Volatility as a Moderator - Repa Nabila; Besse Wediawati; Agus Solikhin (Keizai, 2026)
This study is motivated by significant fluctuations and inconsistent patterns in financial sector stock returns on the Indonesia Stock Exchange (IDX) from 2020–2024, including the paradox of declining returns during the drastic reduction of the Bank Indonesia (BI) rate in 2020. This research aims to analyze the influence of the BI rate and stock liquidity on stock returns, and to examine whether market volatility moderates this relationship. Employing a quantitative method, the sample was selected using purposive sampling, resulting in 40 financial sector companies with a total of 200 observations over five years. Panel data were analyzed using the Generalized Least Square (GLS) approach. The results show that the BI rate does not have a significant effect on stock returns, whereas stock liquidity (Trading Volume Activity) has a positive and significant effect on stock returns. Market volatility is proven to weaken the influence of the BI rate and stock liquidity on stock returns